Guidelines Promoting the Role of Private Detectives to Support the Work of Police Metropolitan, Police Headquarters - Maneewan, Amnuaiporn (Journal for Developing the Social and Community, 2021)
The purpose of this research study of the role of private detectives to support the work of police metropolitan police headquarters, guidelines promoting the role of private detectives to support the work of police metropolitan police headquarters. The research method was structured in-depth interview as a research tool. The population group were lawyers, police policy officer in the investigation and private investigators, totaling 15 people. Analyze data by analyzing the content, then presented with a descriptive narrative. The results of the study revealed that the role of private detectives to support the work of police metropolitan police headquarters by working with the police and help the arrest of the accused person under an arrest warrant to submit to court, behave as a good private detective having professional ethics, understanding of the work to be traced, to solve immediate problems, have patience, information search in good faith, transparency, verifiable, and social responsibility. The guidelines for promoting the role of private investigators there should be legislation establishing clear measures, procedures and duties. Suggestions from the research results: 1. There should be a specific law on private detective business for to help supervise including setting guidelines for private detective business operators. 2. There should be given to private detectives to help assist police find information and facts. 3. There should be training for private investigators to understand the role, code of conduct, access and dissemination of information without violating other persons. 4. There should be private detectives encouraged to volunteer to help inform news of crimes. 5. There should be establish an association or a private detective entrepreneurship council to raise the standard of occupation.